A high performance core for OSI management agents: implementation, simulation and performance evaluation - Rivalino, Matias Júnior (1999)
This article presents a proposal of a multithreaded core for an OSI/ISO management agents including its modeling, simulation and performance evaluation. The proposed model i s compared against another one (unthreaded core) which is the commonly adopted model by the most of the network management systems. All the modeling and simulation process were done at the a gent core level. Therefore the performance evaluation do not consider any effect of the communication layers, dealing with the performance of the activities related to the core of the agents applications.